(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The purpose of the study was to establish the teachers’ views on teaching oral reading fluency in grade 5. The research objective was ‘What are the teachers’ views on teaching oral reading fluency in grade 5?’ A phenomenological research design was used in this study because the research question called for interaction with the participants in their environment. The study sampled six schools, two schools each from Kitwe, Lusaka, and Livingstone towns of Zambia. From these schools, 12 grade 5 teachers were purposively sampled in the study. In this study, grade 5 teachers who were teaching language were interviewed in the selected primary schools in Zambia. The study found that teachers held a view that Oral Reading Fluency (ORF) is a skill that can only be taught in lower primary grades (1-4) and not in upper primary grades (5-6). Teachers have the content knowledge of ORF but lack the pedagogical knowledge to teach fluency to Grade 5 learners. Teachers acknowledge the importance of ORF but deny its power on struggling learners in Grade 5 classrooms. Therefore, non-teaching of oral reading fluency in Grade 5 might be an explanation to why learners still face challenges comprehending what they read in the Zambian primary schools. It was then recommended that teachers should ensure they teach ORF to enable learners to become fluent in reading whilst in primary schools.